A deep view of dynamics of teleworking in Panama - Frassati-Mora, Gianna; Anaya, Maria Teresa; Bonilla, Enereyda (Revista Venezolana de Gerencia, 2024)
Teleworking has accelerated in the last three years, although the advantages of this modality can be valuable, its application still requires legal and practical aspects in order to carry out the activities in an agile and appropriate manner. In this sense, its objective was to analyze of telework modality in Panama. To this end, a study was conducted using the positivist paradigm with quantitative, non-experimental, cross-sectional field methodology, with the instrument structured in four dimensions. The research design was descriptive-correlational, field-based, applied, using a stratified probability sample, using the economically active population of the country as an estimate. The sample was calculated using Bravo’s (1994) formula, with a sampling error of 5%, resulting in a total number of 399 participants from different economic sectors where teleworking is possible, such as education, information and communication technology, banking and insurance. The overall conclusion of the study is that the introduction of teleworking in Panama has been effective. However, the impact of teleworking on employees’ well-being can be considered negative and it is recommended to incorporate best practices to mitigate the impact in terms of labor legislation and workers’ well-being in terms of mental health.